Retrovirus Integration Database (RID): a public database for retroviral insertion sites into host genomes. Issue 1 (December 2016) - Shao, Wei; Shan, Jigui; Kearney, Mary; Wu, Xiaolin; Maldarelli, Frank; Mellors, John; Luke, Brian; Coffin, John; Hughes, Stephen
Abstract The NCI Retrovirus Integration Database is a MySql-based relational database created for storing and retrieving comprehensive information about retroviral integration sites, primarily, but not exclusively, HIV-1. The database is accessible to the public for submission or extraction of data originating from experiments aimed at collecting information related to retroviral integration sites including: the site of integration into the host genome, the virus family and subtype, the origin of the sample, gene exons/introns associated with integration, and proviral orientation. Information about the references from which the data were collected is also stored in the database. Tools are built into the website that can be used to map the integration sites to UCSC genome browser, to plot the integration site patterns on a chromosome, and to display provirus LTRs in their inserted genome sequence. The website is robust, user friendly, and allows users to query the database and analyze the data dynamically. Availability:https://rid.ncifcrf.gov ; orhttp://home.ncifcrf.gov/hivdrp/resources.htm .